The Relationship of the Surabaya Diocese's Cadre Development Program within the Socio-Cultural Domain - Yuendzi Santa Aurell; Parji Parji; Yuni Harmawati (Borong Newinera Publisher, 2026)
This study aims to examine the relationship between the cadre program organized by the Diocese of Surabaya and the socio-cultural domain in Civic Education. This program not only honors spiritual and leadership aspects, but also instills civic values through community-based activities, social dialogue, and cross-cultural experiences, and aims to shape the character, leadership skills, and active participation of young Catholics in community life. The research approach used is descriptive qualitative with a case study method. Data collection techniques were conducted through interviews, observations, and documentation. Data analysis used triangulation techniques by comparing interviews, observation, and documentation data. The results of the study show that this program effectively instills civic values, such as leadership, communication, and integrity, which are closely related to civic knowledge, civic skills, and civic dispositions that result in civic engagement. This program contributes significantly to civic character education that is relevant to the needs of the times. This study recommends the importance of integrating socio-cultural citizenship practices into youth development programs.